The Effect of Sensory Marketing on Customer Behavior : The impact of product classes on product evaluations - Ask, Alexander; Svensson, Oskar (2015)
In today's highly competitive marketplace, traditional marketing has lost its effectiveness. Since rational and functional attributes are becoming more homogeneous, and customers are exposedto thousands of advertisements on a daily basis, there is a need for a paradigm shift in themarketing approach. With the senses being instrumental for our interpretation of the world,sensory marketing has the potential to improve the effectiveness of marketing in a cost efficient manner.To further develop the understanding of sensory marketing, an investigation of the sensorial impact on product evaluation has been conducted. The emphasis has been to explore potential differences between different product classes. This was examined by investigating high- and low involvement products influence for three senses: vision, olfactory, and haptic. Threeexperiments were conducted with students at Luleå University of Technology, during whichthe students were exposed to different sensorial stimuli. After the experiments, a focus groupwas held in order to discuss the participants’ thoughts and feelings. The collected data indicates that sensory marketing, to an extent, is dependent on the specific product it is used for. It ismore important than previous research has indicated to consider product specific factors in order to avoid inefficient marketing strategies.All in all, the research provides additional knowledge that further develops the field of sensorymarketing by presenting supporting evidence for the importance of sensorial input during product evaluations. With stimuli that is tailored towards the products, it is possible to positively influence customers’ product evaluations, which can be very beneficial for practitioners. Validerat; 20150610 (global_studentproject_submitter)